Assesing the Accuracy of Translation Result of Kataku Version 1.1 and Transtool 10 from English to Indonesian and Its Implication on Language Teaching - Yuwono, Dolar; Nababan, M.R.; Tarjana, Sri Samiati; Wiratno, Tri (IAIN Samarinda, 2018)
This journal is aimed at investigating the accuracy of Kataku Version 1.1 and Transtool10 Rar and knowing its benefit for teaching writing. This is important because Computer Assisted Translation (CAT) has become a need and practical translation tool as a software to translate source language text (SL) into the target language (TL). The number of users of both devices requires a proof of whether both tools are qualified enough to translate from SL to TL. This study used descriptive qualitative methods with data collection techniques using documents, interviews and questionnaires. While the data analysis technique used component analysis consisting of four parts, that is, domain, taxonomy, component and cultural theme analysis using â€œcriteria based samplingâ€ 1 to 3, that is, accurate (3), less accurate (2) and not accurate (1). The results showed the quality of the